Defences to tortious and contractual liability in French law - Steel, S (Hart Publishing, 2019)
Extract: This chapter is in two sections. Section I examines general issues surrounding defences in French tort and contract law, comparing the position to that in English law. Section IA considers the meaning of the term ‘defence’, and identifies a number of concepts to which the term refers. The focus of the chapter is upon facts which defeat liability even if the elements of a rule are satisfied (‘the externalist definition’) and, to the extent they differ, facts which defeat or restrict liability, which are for the defendant to prove (‘the proof-based definition’) . Section IB shows that both English law and French law contain defences in these senses. Section IC considers whether the concept of a defence is recognised as part of the law or as an organising...